The low-latitude sodium layer: comparative data from lidar observations at Hainan, China and São Paulo, Brazil - Fang Wu; Jing Jiao; GuoTao Yang; LiFang Du; ZhengKuan Liu; HaoRan Zheng; JiXin Guo; ShaoHua Gong; YaJun Zhu (Earth and Planetary Physics)
Physical and chemical processes observed in the mesosphere and thermosphere above the Earth’s low latitudes are complex and highly interrelated to activity in the low-latitude ionosphere. Metallic sodium detected by lidar can yield clues to dynamic and chemical processes in these spatial layers above the Earth’s atmosphere. This paper is based on sodium layer data collected at two low-latitude stations, one in the northern hemisphere and one in the southern. The low-latitude sodium layer exhibits conspicuous seasonal variations in shape, density, and altitude; these variations are similar between Earth’s hemispheres: sodium layer density at both stations reaches its seasonal maximum in autumn and minimum in summer. However, maximal Na density over Brazil is greater than that over Hainan. Nocturnal variations of Na density above the two low-latitude stations are also similar; at both, maxima are observed before sunrise. Some variations of the Na layer over Brazil that differ from those observed in the northern hemisphere may be related to the South Atlantic Magnetic Anomaly (SAMA) or fountain effect. We suggest that low-latitude Na layer data may provide useful additional evidence that could significantly improve the low-latitude part of the WACCM-Na model.